Creative citizenship and the public policy process - Lee Stephen (Cultural Science)
This paper raises the question of how a proposition such as ‘Creative Citizenship’ might fit into the UK policy landscape. It begins by describing the appeal of such a concept to politicians keen to latch on to an idea that positions the electorate as creative, engaged and technologically astute. However, Creative Citizenship runs the dangers of being yet another fashionable, wide-ranging concept that political leaders tend to be ‘mesmerised’ by as they write up their election manifestos. Initiatives based on such ideas rarely meet with success and therefore for Creative Citizenship not to meet with the same fate it must be more clearly defined. The paper outlines a manifesto for Creative Citizenship that would allow for a more targeted application on those areas of public policy where the features of Creative Citizenship might be seen to be making a positive difference.